Facile Fabrication of Highly Efficient Photoelectrocatalysts MxOy@NH2‐MIL‐125(Ti) for Enhanced Hydrogen Evolution Reaction. Issue 23 (19th June 2019) - Fiaz, Muhammad; Kashif, Muhammad; Majeed, Saadat; Ashiq, Muhammad Naeem; Farid, Muhammad Asim; Athar, Muhammad
Abstract: Highly efficient amine functionalized Mx Oy @NH2 ‐MIL‐125(Ti) (Mx Oy =MnO2, Fe2 O3, Co3 O4, NiO, CuO and ZnO) photoelectrocatalysts have been synthesized by using a simple and cost effective synthetic approach through in‐situ incorporation of pre‐synthesized metal oxide nanoparticles into NH2 ‐MIL‐125(Ti) MOF via hydrothermal method. All the synthesized samples have been characterized by Powder X‐ray Diffraction, Fourier Transform Infrared Spectroscopy, Scanning Electron Microscopy, Energy Dispersive X‐ray Spectrometry, Elemental Mapping, UV‐Vis Spectroscopy and N2 ‐adsorption isotherm. It has been found that incorporation of nanoparticles into porous MOF decreased the band gap, reduced the electron‐hole pair recombination and enhanced the efficient absorption of visible light. Hydrogen evolution reaction is evaluated by Cyclic voltammetry and linear sweep voltammetry studies at 100 mV/s and 1 mV/s, respectively. Amongst various synthesized samples, CuO@NH2 ‐MIL‐125(Ti) required lowest overpotential of 146 mV to achieve −5mAcm −2 current density as compared to 226 mV for bare NH2 ‐MIL‐125(Ti). Moreover, Mx Oy @NH2 ‐MIL‐125(Ti) samples showed lower onset potential for hydrogen evolution reaction as compared to bare NH2 ‐MIL‐125(Ti). Chronoamperometric measurements of all these samples showed their stability for 600 seconds at constant applied voltage of 1.5 V. Abstract : In this reported article, highly efficient photoelectrocatalysts Mx Oy @NH2 ‐MIL‐125(Ti) have been synthesized via facile hydrothermal method for hydrogen evolution reaction from water splitting. It has been observed that among various synthesized photoelectrocatalysts, CuO@NH2 ‐MIL‐125(Ti) showed better HER activity as it showed lowest onset potential more close to zero, required lowest overpotential to achieve the targeted −5mAcm −2 current density as compared to bare NH2 ‐MIL‐125(Ti) and other Mx Oy @NH2 ‐MIL‐125(Ti) photoelectrocatalysts.